Chemically-biased diffusion and segregation impede void growth in irradiated Ni-Fe alloys. Issue 2 (April 2019) - Barashev, Alexander; Osetsky, Yuri; Bei, Hongbin; Lu, Chenyang; Wang, Lumin; Zhang, Yanwen
Highlights: Chemically-biased diffusion creates Ni segregation near mobile defect sinks in Ni-Fe alloys. Segregation profiles near voids and interatitial loops suppress their interaction with vacancies. Interstitial loops grow while void nuclei collapse into Ni-rich precipitates in the damage region. Ni segregation on voids and interstitial loops lead to Ni depletion of the matrix between sinks. Vacancies migrate out and form voids beyond the damaged area, inaccessible to SIAs. Abstract: Recent irradiations of Ni-Fe concentrated solid solution alloys have demonstrated significant improvement of radiation performance. This improvement is attributed to redistribution of the alloying elements near sinks of point defects (voids, dislocations) due to chemically-biased atomic diffusion, where vacancies have preference to migrate via Fe atoms and interstitials via Ni atoms. In Ni-Fe, all sinks are enriched by Ni atoms, which strongly affects further interactions of radiation-produced mobile defects with voids and dislocations, hence void growth and dislocation climb. Ni-decorated sinks interact stronger with interstitial atoms than vacancies, which enhances dislocation loops growth. At the same time, Ni segregation creates Fe-enriched "channels" for vacancy migration out of the damage region to agglomerate in the outer regions, inaccessible to interstitial atoms. Strong effect of chemically-biased diffusion is supported by transmission electron microscope characterization and calls for special attention in designing alloys with desired properties through tuning defect mobilities.